Dietary practice and nutritional status of senior citizens of Lomanthang rural municipality of Mustang district. - Gurung,Tsering Wangmo (2020)
ABSTRACT: Introduction: Senior Citizen Act, 2068 of Nepal defines senior citizens as the population who has completed their 60 years of age. Population ageing is the dynamic process of demo graphic and socioeconomic transformation which reflects the increase in the share of the elderly on the total population. The ageing population is expanding at great pace through-out the globe and the proportion of this age group is expected to double (22%) by 2050. In Nepal, the CBS (2011) reported that the percentage of population aged 60 years and above increased from 6.5% during 2001 to 8.1% in 2011. Unlike developed countries, ageing is rapidly increasing in developing countries like Nepal. Factually, ageing have both the merits and demerits for every nation. Ageing are very much likely to be accompanied with vast list of morbidities leading to health, financial and social burden to the nation. Methodology: A community based cross-sectional study was conducted among 210 senior citizens of Lomanthang RM of Mustang district from August 2020 to June 2021. Simple random sampling technique was conducted. Face to face interview was conducted for data collection. A semi-structured questionnaire comprising different section of questions was used. The screening tool mini nutritional assessment (MNA) was used either. Tool was developed in both English and Nepali language with consultation with supervisor and was pretested among 10% of participants and pretesting was done at households nearby Pokhara University. Ethical approval was obtained from Institutional Review Committee, Pokhara University. Permission was taken from Lomanthang Rural Municipality and informed consent was taken from each participants. EPIDATA and SPSS were used for data management and analysis. Results: This study found that majority of participant was young olds with age group 60-70 and female participants were more than male. All the participants were Buddhist and almost all were Gurung and majority was living in joint family. Similarly, majority of participants were married and followed by widow and widower. 83.4% of participants have given birth to more than three children. Similarly, 91% of participants were illiterate and most of the participants did agriculture as their past occupation. In the case of dietary practices, more than 50% of participants consume almost all types of food such as meat, fruits, green vegetables, milk and milk products, pulses, excluding fish, egg, junk food and food prepared outside house in general. The consumption of all the above mentioned food is mostly consumed less than 3 times per week by majority. Moreover, majority of the participants have the habit of taking all the four time major meals i.e Breakfast, Lunch, Snack and Dinner daily. Intake of energy giving food is high in comparison to body building food and body protective food in all the four major meal of majority of participants. The intake of body protective food is noticeably low in all four major meals. 44.3% of participants were at risk of malnutrition followed by 28.6% of participants malnourished and 27.1% of participants at normal nutrition. Positive changes in both smoking and alcoholism were witnessed with decrease in the number of smoking and alcohol consuming participants in past and at present. In the present study, we observed that many of the socio-demographic variables such as age, sex, family types, marital status and educational status were significantly associated with nutritional status of participants. Similarly, only green vegetable is associated with nutritional status. Conclusion: From the study, we conclude that prevalence of population at risk of malnutrition is relatively high in comparison to many studies conducted within Nepal. The prime reason could be due to remoteness and difficult landform structure.